2008
DOI: 10.1068/p5620
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Potentials, Reaction Time, and Response Selection of Skilled and Less-Skilled Cricket Batsmen

Abstract: The differences in P300 latency, P300 amplitude, response selection, and reaction time between skilled and less-skilled cricket batsmen have been investigated. Eight skilled and ten less-skilled right-handed batsmen each viewed 100 in-swing, 100 out-swing, and 40 slower deliveries displayed in random sequence from projected video footage whilst their responses and electroencephalograms were recorded. Logistic regression was used to derive a discriminative function for the P300 data. This was done to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
2
17
1
5
Order By: Relevance
“…There are scientific studies confirming the association between observations of motor activities and the mechanisms of attention in sports with high perceptual requirements. For example, Taliep et al (2008) when analyzing the efficiency of attention processes in cricket players, observed a lower amplitude of the P300 wave (recognized as a psychophysiological measure of attention processes), faster reaction time and better discrimination and recognition of correct stimuli (film presentation of different kinds of ball throws). The authors suggested that players training sport with high perceptual requirements engaged less attention during recognition of the type of throw than other persons.…”
Section: Discussionmentioning
confidence: 99%
“…There are scientific studies confirming the association between observations of motor activities and the mechanisms of attention in sports with high perceptual requirements. For example, Taliep et al (2008) when analyzing the efficiency of attention processes in cricket players, observed a lower amplitude of the P300 wave (recognized as a psychophysiological measure of attention processes), faster reaction time and better discrimination and recognition of correct stimuli (film presentation of different kinds of ball throws). The authors suggested that players training sport with high perceptual requirements engaged less attention during recognition of the type of throw than other persons.…”
Section: Discussionmentioning
confidence: 99%
“…La experiencia influye en el rendimiento, dando lugar a una toma de decisiones más rápida y precisa. Por tanto, los resultados son confirmados por otros estudios que afirman que los deportistas expertos demuestran habilidades superiores en el uso de información visual anticipada, en cuanto a anticipación de la dirección de un móvil en una variedad de deportes diferentes (Ando, Kida y Oda, 2001;Kioumourtzoglou et al, 1998;Taliep et al, 2008).…”
Section: Discussionunclassified
“…El intento de observar todos los movimientos que suceden en un deporte, exige utilizar la visión de forma adecuada. Los científicos investigan si las destrezas visuales que poseen muchos deportistas pueden ser adquiridas a través de la práctica y, particularmente, si los deportistas expertos poseen una mayor ventaja sobre los deportistas menos expertos (Abernethy, Gill, Parks y Packer, 2001;Overney, Blanke y Herzog, 2008;Savelsbergh et al, 2002;Singer, Cauraugh, Chen, Steinberg y Frehlich, 1996;Taliep et al, 2008;Williams y Elliott, 1999).…”
Section: Introductionunclassified
“…Firstly, advanced visual perceptual processing and visual-motor skills are important for skilled batting performance. [8][9][10][11] There is evidence indicating that in South Africa, BA children (aged between 4 and 7 years) have weaker visual-motor skills than W children. 12 This could hinder their batting development.…”
Section: Discussionmentioning
confidence: 99%